Language is the soul of our nation - Abd Razak, Dzulkifli (2008)
THE issue of the social contract, or rather the need to revise it, has risen again. This matter was last raised by a minister a few years ago, who has since retired. The social contract has been a convenient political football from time to time. The argument seems to be that after 50 years of independence, the contract is not considered relevant any more. This, of course, is a moot point that must be examined in the context of preindependent Malaya. The social contract should be taken as an important negotiated document that eventually led to the birth of a new independent sovereign nation.